NGHIÊN CỨU CHẾ TẠO MÀNG MỎNG OXIT Er¬2O3 BẰNG PHƯƠNG PHÁP MOCVD TỪ TIỀN CHẤT Er(acac)3.phen - Nguyệt, Triệu Thị; Miền Trung, Huỳnh Thị (Vietnam Journal of Chemistry, 2012)
In this paper, we report the structural and morphological properties of Er2O3 thin film grown on glass via metal-organic chemical vapor deposition method by making use Er(acac)3.phen as the precusor. Some characterations of as-deposited and after-annealed films have been investigated by XRD and SEM methods. The obtained results shown that film annealed at 450oC is crystallined with cubic phase and partical gains were calculated to be around 10 nm by the scherrer equation.